Research on Fractal Model of Load Distribution and Axial Stiffness of Planetary Roller Screw Mechanism Considering Surface Roughness and Friction Factor. Issue 4 (24th January 2022) - Du, Xing; Chen, Bingkui; Liu, Rongrong; Li, Chaoyang
Abstract: The effects of surface roughness and material properties of the planetary roller screw mechanism (PRSM) on the axial stiffness and load distribution are rarely studied. In this paper, the load distribution model is presented by incorporating into friction factor and surface microtopography. The microcontact model is built by considering elastic and plastic regimes to calculate the total actual contact area. Moreover, the load distribution model is modified by introducing surface microcontact coefficient. Then, the influences of the nut position, fractal dimension, fractal roughness, friction factor, axial load, and material yield strength on the axial stiffness and load distribution are studied in detail. The numerical results show that the axial stiffness rises with the increment of the nut position, axial load, fractal dimension, and yield strength, and reduces with the fractal roughness and friction factor increasing. In addition, the uniformity of the load distribution increases with the increment of the fractal roughness, and drops with the increase of the fractal dimension and material yield strength. This investigation lays the foundation for the design, manufacturing, and use of the PRSM. Abstract : The axial stiffness and load distribution models suitable for the planetary roller screw mechanism are presented by considering the surface microtopography and friction factor. The multiscale microcontact model is modified by introducing the surface microcontact coefficient. The influences of the nut position, fractal dimension, and fractal roughness on the axial stiffness and load distribution are furtherly studied.